2015
DOI: 10.1523/jneurosci.3890-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Rate-Dependent Effects of Oral Methylphenidate on Impulsivity and D2/3Receptor Availability in the Striatum

Abstract: We have previously shown that impulsivity in rats is linked to decreased dopamine D 2/3 receptor availability in the ventral striatum. In the present study, we investigated, using longitudinal positron emission tomography (PET), the effects of orally administered methylphenidate (MPH), a first-line treatment for attention deficit hyperactivity disorder, on D 2/3 receptor availability in the dorsal and ventral striatum and related these changes to impulsivity. Rats were screened for impulsive behavior on a five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 57 publications
8
46
1
Order By: Relevance
“…To our knowledge, a sex difference in visual discrimination learning in untreated rats has not been reported before. Sex differences in previous studies have been noted in the areas of increased addiction vulnerability in male rats (Crawford et al 2011), higher levels of anxiety (Iñiguez et al 2010), and higher levels of impulsivity in male vs. female rats (Caprioli et al 2015). Rodent females, like human females, mature earlier than males: on average the development of genitalia and activation of sexual organs occurs 4–8 d faster (Spear 2015).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To our knowledge, a sex difference in visual discrimination learning in untreated rats has not been reported before. Sex differences in previous studies have been noted in the areas of increased addiction vulnerability in male rats (Crawford et al 2011), higher levels of anxiety (Iñiguez et al 2010), and higher levels of impulsivity in male vs. female rats (Caprioli et al 2015). Rodent females, like human females, mature earlier than males: on average the development of genitalia and activation of sexual organs occurs 4–8 d faster (Spear 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that MPH increases impulsivity in rats prescreened to be ‘low-impulsive’ before exposure (Caprioli et al 2015). Accordingly, a subset of our adult rats pretreated with MPH in adolescence may have had difficulty attending to the task demands in reversal learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early on, (Dalley et al 2007) it was noticed that cocaine self-administration appeared to blunt the high impulsivity expressed as increased premature responding; this was reminiscent of effects of agents such as methylphenidate (Ritalin ® ) in combating impulsive behavior in ADHD and presumably arises from the effects of these drugs to increase catecholamine (i.e., DA and noradrenaline [NA] levels) in the synaptic cleft, by virtue of their actions, for example, to block the DA and NA transporters and hence block the reuptake of these neurotransmitters. More recently, this has been explored in further detail both with intravenously self-administered cocaine ) and orally administered methylphenidate (Caprioli et al 2015). In both cases, the stimulant drug reduced premature responding significantly in high-impulsive rats while increasing it in rats with lower (i.e., normal) baseline levels of premature responding (Fig.…”
Section: Chemical Neuromodulation Of Waiting Impulsivitymentioning
confidence: 99%
“…This deficit (left scans) is corrected by cocaine and methylphenidate (right scans) with a corresponding reduction in behavioral impulsivity in the 5CSRTT (b, d, respectively). From Caprioli et al (2015) and Caprioli et al (2013) with permission…”
Section: Chemical Neuromodulation Of Waiting Impulsivitymentioning
confidence: 99%